* Are uk gastroenterology trainees confident in managing hepatology?. (13th March 2011) - Patanwala, I; Haycock, A; Hudson, M; ,
Abstract : Introduction: Trainee self-reported confidence levels have been used to assess adequacy of training and identify areas in training programs that are in need of improvement1 . Currently, there is no data on how confident UK gastroenterology trainees are in managing various liver related conditions. Methods: We surveyed all trainees in gastroenterology and hepatology in UK in March 2010 using an online questionnaire. Information on whether trainees felt confident about managing various liver related conditions encountered in everyday practice and in tertiary level care was collected and data analysed using MS Excel and SPSS. Results: 283 of 489 (58%) trainees responded. There was no statistical difference in the proportion of trainees in each year of training from year 1 to year 5 (p=0.185). 91% of respondents were specialist trainees or specialist registrars. The proportion of trainees lacking confidence in managing routinely encountered liver related illness (abnormal liver function tests, decompensated Chronic liver disease, medical management of portal hypertension, Insertion of a Sengstaken Blakemore tube for acute variceal bleeding), specialised liver related illness encountered in secondary care (alcoholic hepatitis, autoimmune hepatitis, hepatorenal syndrome, treatment of acute liver failure in a secondary care setting, referral for TIPS and referral for OLTx consideration) and those encountered in tertiary/specialised hepatology centres (long term management of a liver transplant recipient and managing acute liver failure in a tertiary care environment including management of liver disease in critical care) decreased as the total time spent in training increased. Exposure to training in a liver unit providing comprehensive liver services significantly decreased the proportion of trainees that lacked confidence in managing these conditions. However, even with such training, almost 1 in 10 trainees in year 4 or more did not feel confident about inserting a Sengstaken Blakemore tube, managing acute liver failure in secondary care, managing alcoholic hepatitis or referring for OLT and TIPSS; 1 in 3 was not confident about managing liver disease in the critical care setting and about half were not confident about being able to manage acute liver failure in a tertiary care setting. Conclusion: The hepatology component of the unified gastroenterology-hepatology training in the UK is lacking in advanced hepatology training. Incorporating liver unit level hepatology exposure into every trainees curriculum, to both increase and standardise hepatology training throughout the UK should be mandatory.